Kata Sapaan Bahasa Batak Toba Dialek Desa Lumban Sihite Kecamatan Laeparira Kabupaten Dairi Provinsi Sumatera Utara - Rosa Anna Lumban Gaol; Jamilin Tinambunan (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
The use of greeting words is a method used to reprimand, greet, invite conversation, and so on. The development of science and technology affects changes in the use of kinship words in the Toba Batak language in Lumban Sihite Village, Laeparira District, Dairi Regency. This study aims to describe the use of kinship and non-kinship greeting words in the Toba Batak language dialect of Lumban Sihite Village, Laeparira District, Dairi Regency. The research problems that the writer examines are (1) How is the use of kinship words in the Toba Batak language in Lumban Sihite Village, Laeparira District, Dairi Regency? (2) How is the use of non-kinship greetings in the Toba Batak language in Lumban Sihite Village, Laeparira District, Dairi Regency?. This research methodology uses descriptive methods to identify research problems and qualitative approaches. The results of the research that the authors found showed that the use of greeting words in the Toba Batak language in Lumban Sihite Village, Laeparira District, Dairi Regency to fellow relatives was 45 greeting words. While the use of non-kinship greeting words in the Toba Batak language in Lumban Sihite Village, Laeparira District, Dairi Regency as many as 9 greeting word.